The awareness level of residents on the use of renewable energy resources for domestic use in Setapak, Kuala Lumpur - Ibrahim, Mohammad Bassam (Kulliyyah of Architecture and Environment Design, International Islamic University Malaysia, 2018)
The use of renewable energy sources has proved environmental, economic, and political benefits to worldwide countries. Malaysia is one of these countries which considered renewable energy as the fifth fuel source in Malaysia in 2001. However, the generated energy from renewable sources is still below the targeted value of cumulative national energy plans in Malaysia. Awareness of the benefits of using renewable energy technologies helps on growing the use of renewable energy. Despite the possibly positive contribution of awareness level of the Malaysian population to the use of renewable energy technologies, few research studies were carried out to define the level of awareness of locals and its influence on growth rates of using renewable energy technologies. This study aimed at measuring the level of awareness of local residents of the area of Setapak in Kuala Lumpur about renewable energy sources and technologies for domestic use. It also aimed at evaluating the effect of this level on the increase of renewable energy projects and to identify the problems that face people who have used renewable energy solutions that arise from the lack of awareness. A total of 50 respondents to a questionnaire from Setapak were involved in this study. The study found from the analysis that it was that Setapak residents are familiar with renewable energy sources and technologies as most have a good background regarding renewable energy definition, usage and importance. Also, residents with higher levels of awareness of renewable energy were more likely to be aware of renewable energy usage incentives and mechanisms in Malaysia and more likely to engage in positive practice towards renewable energy sources and technologies use. However, the factors which were expected to affect the level of awareness of renewable energy especially age, income level, and level of education do not have a significant impact on the level of awareness. New generations, which have higher exposure to knowledge and higher levels of education do not have a higher awareness level. Finally, the cost of renewable energy technologies and little knowledge of renewable energy in Malaysia, energy policies and mechanisms in Malaysia, and companies who provide renewable energy sources were reported by users of renewable energy solutions as main obstacles that face future users. The study recommends the inclusion of awareness topics about renewable energy in environmental awareness programs which are guided by the government, also better marketing plans of Energy policies and mechanisms in Malaysia such as FiT and NEM mechanisms which proved effective. It was also recommended that more efforts should be spent on financing individual renewable energy solutions. Finally, encouraging more studies on awareness level evaluation of renewable energy among locals on larger scales and guided by local institutes and governmental funds.